2021
DOI: 10.1242/jeb.241109
|View full text |Cite
|
Sign up to set email alerts
|

Body size affects immune cell proportions in birds and non-volant mammals, but not bats

Abstract: Powered flight has evolved several times in vertebrates and constrains morphology and physiology in ways that likely have shaped how organisms cope with infections. Some of these constraints likely have impacts on aspects of immunology, such that larger fliers might prioritize risk reduction and safety. Addressing how the evolution of flight may have driven relationships between body size and immunity could be particularly informative for understanding the propensity of some taxa to harbor many virulent and so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 87 publications
(115 reference statements)
0
4
0
Order By: Relevance
“…Although variations linked to immune-senescence and -maturation in circulating leukocytes have been validated in several chiropteran species, e.g., P. giganteus ( McLaughlin et al, 2007 ; Schneeberger et al, 2014 ) and P. poliocephalus ( Edson et al, 2018 ) and other mammals ( Aminzadeh and Parsa, 2011 ), we could not detect age-related differences for E. helvum or R. aegyptiacus . Interestingly, it has been recently demonstrated that the number of circulating immune cells (especially neutrophils and lymphocytes) is size-independent in bats and did not differ significantly among 64 different bat species ( Cornelius Ruhs et al, 2021 ). Bats are the only mammals capable of active flight, which represents a demanding way of locomotion with a high oxygen requirement.…”
Section: Discussionmentioning
confidence: 99%
“…Although variations linked to immune-senescence and -maturation in circulating leukocytes have been validated in several chiropteran species, e.g., P. giganteus ( McLaughlin et al, 2007 ; Schneeberger et al, 2014 ) and P. poliocephalus ( Edson et al, 2018 ) and other mammals ( Aminzadeh and Parsa, 2011 ), we could not detect age-related differences for E. helvum or R. aegyptiacus . Interestingly, it has been recently demonstrated that the number of circulating immune cells (especially neutrophils and lymphocytes) is size-independent in bats and did not differ significantly among 64 different bat species ( Cornelius Ruhs et al, 2021 ). Bats are the only mammals capable of active flight, which represents a demanding way of locomotion with a high oxygen requirement.…”
Section: Discussionmentioning
confidence: 99%
“…The absolute number of each white blood cell type was then determined by multiplying its relative abundance by the estimated TWBC count ( Becker et al, 2021 a ), and we derived NL ratios. A subset of the hematology data from 2017 and 2018 were published previously ( Cornelius Ruhs et al, 2021 ; Becker et al, 2021 a ).…”
Section: Methodsmentioning
confidence: 99%
“…Species and sex were added as covariates given their documented influence on variation in immune function (Arriero et al., 2015 ; Tieleman et al., 2005 ). The body mass index was also added as a covariate as mass and size can influence immune cell proportions and metabolic rate (Cornelius Ruhs et al., 2021 ). Finally, relative arrival date was added as a covariate as early migrating individuals may differ in immune function from late migrating individuals (Hegemann et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%